PENGARUH QUALITY OF WORK LIFE, KOMITMEN KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA KANTOR PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROVINSI SULAWESI TENGGARA - ASDA BKKBN (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to examine and analyze the Effect of Quality of Work Life, Work Commitment on Employee Performance through Job Satisfaction at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province. This research is a quantitative approach. The population in this study were employees at the Representative Office of the National Population and Family Planning Agency of Southeast Sulawesi Province with a sample of 58 employees. The analytical tool used is Warp Partial Least Square (PLS). The results showed that (1) Quality of Word Life had a positive and significant effect on employee performance, (2) Quality of Work Life had a positive and significant effect on employee job satisfaction, (3) Work commitment had a positive and insignificant effect on employee job satisfaction ( 4) Work commitment has a positive and significant effect on employee performance. (5) Job satisfaction has a positive and significant effect on employee performance. (6) Job Satisfaction plays a role in mediating Quality of Work Life on Employee Performance. (7) Job satisfaction does not mediate work commitment to employee job satisfaction.